Communicating the bilingual school from the soils we breathe: Voices and community practices of chinantecos teachers in Oaxaca - Miguel Dario Hidalgo Castro; Roberto Sánchez Linares; Pablo Ojeda Carrillo (Universidade Federal do Norte do Tocantins, 2023)
This paper deals with an experience on the trajectory of Community Education located in Chinantec communities in the State of Oaxaca. Chinantec teachers have given themselves the historical task of building educational projects from the community, actions that have allowed them to unravel the routes to decolonize education. The symmetrical interaction between the school and the communities has been strengthened through years of work. These school forms and practices also consider their own topics that allow making vindicating processes of community dynamics and structures, such as rural community knowledge and knowledges that are generated on a daily basis, communality is pointed out as a practical-explanatory horizon that helps to articulate community knowledge and knowledges in school practices, then other educational experiences from a conception of collective learning -by understanding-. "Communalizing education", among others, is a principle of the pedagogical movement that guides the educational work among the Chinantecos as community subjects. We have to mention that the pedagogical accompaniment and the link with the political movement of teachers has brought us closer to important data and testimonies from the observation involved and interviews for the elaboration of this localized educational experience.